Minimally invasive ingestible device to perform anti-bacterial phototherapy in the stomach. (September 2016) - Romano, Giovanni; Tortora, Giuseppe; Calusi, Silvia; Orsini, Barbara; Gnerucci, Alessio; Fusi, Franco
Abstract : Introduction: In the framework of the growing rate of antibiotic-resistance, new therapeutic solutions are being considered against bacterial infections, among which photodynamic therapy (PDT) is a very attractive perspective. In recent years, innovative solutions for endoscopic illumination have been studied, e.g. for catheter infections, pancreas tumours and stomach infections by Helicobacter pylori (Hp) . Hp colonizes the human stomach with a worldwide infection prevalence exceeding 50%, besides being a class 1 carcinogen agent (World Health Organization). Currently, Hp infection is treated with pharmacologic therapies, showing high failure rates mainly due to antibiotic resistance. To overcome this limitation, endoscopic PDT devices have been tested. However, they exhibit clear disadvantages, namely great invasivity and adverse effects. Purpose: To design and characterize a non-invasive light-emitting device to perform Hp phototherapy: an ingestible "LED antibiotic", exploiting the presence of endogenous Hp photosensitizers. Materials and methods: Merging experimental and simulation methods we obtain the light action spectrum for Hp phototherapy in the gastric environment. We have designed and assembled the pill containing LED sources, a battery and electronic board. Capsule emission parameters are measured by an integrating sphere and in vitro Hp irradiation performed. Results: The action spectrum for Hp phototherapy is peaked in the violet and red spectrum regions. Capsule prototypes show emission parameters compatible with in vitro Hp eradication (>99% killing). Conclusion: Our device has shown emission spectrum, intensity and duration compatible with an effective phototherapy of Hp, considering also the treatment repeatability (5–10 capsules in 2–3 weeks). Future clinical trials are envisaged. Disclosure: GR, GT, BO and FF disclose being also Probiomedica srl (www.probiomedica.com ).